CUSTOMER EXPECTATION AND SATISFACTION OF HOUSEKEPING SERVICES: A BIBLIOMETRIC ANALYSIS OF DATA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Customer Expectation and Satisfaction have  always been an engrossing and important topic  of interest for the hospitality reseachers. It is  important because it helps in understanding  the needs of the customers and then generating  and providing services accordingly. The purpose  of this research paper is to provide the analytic  data of the work that has been done in the  field of customer expectation and satisfaction  in hospitality industry. Using the keywords  Hospitality and Customer Satsfaction a  bibliometric analysis of 415 published research  articles of 21st centaury. From the above  mentioned research articles the most cited  countries, authors, most referred articles and  other parameters.
Keywords: Customer Satisfaction; Hospitality Services; Review and Customer Expectation